Ambiviricota , a novel ribovirian phylum for viruses with viroid-like properties - Kuhn, Jens H; Botella, Leticia; de la Peña, Marcos; Vainio, Eeva J; Krupovic, Mart; Lee, Benjamin D; Navarro, Beatriz; Sabanadzovic, Sead; Simmonds, Peter; Turina, Massimo (Journal of virology, 2024)
Fungi harbor a vast diversity of mobile genetic elements (MGEs). Recently, novel fungal MGEs, tentatively referred to as 'ambiviruses,' were described. 'Ambiviruses' have single-stranded RNA genomes of about 4-5 kb in length that contain at least two open reading frames (ORFs) in non-overlapping ambisense orientation. Both ORFs are conserved among all currently known 'ambiviruses,' and one of them encodes a distinct viral RNA-directed RNA polymerase (RdRP), the hallmark gene of ribovirian kingdom . However, 'ambivirus' genomes are circular and predicted to replicate via a rolling-circle mechanism. Their genomes are also predicted to form rod-like structures and contain ribozymes in various combinations in both sense and antisense orientations-features reminiscent of viroids, virusoids, ribozyvirian kolmiovirids, and yet-unclassified MGEs (such as 'epsilonviruses,' 'zetaviruses,' and some 'obelisks'). As a first step toward the formal classification of 'ambiviruses,' the International Committee on Taxonomy of Viruses (ICTV) recently approved the establishment of a novel ribovirian phylum, , to accommodate an initial set of 20 members with well-annotated genome sequences.